Decision-making and visual search strategy of baseball catchers in a situation of giving directions on a play - Kikumasa, A.; Kokubu, M. (Japanese Journal of Sport Psychology, 2018)
The present study aimed to clarify the strategy of decision-making and visual search of baseball catchers in a situation that requires directions to teammates on a play. Collegiate baseball catchers, fielders, and non-ballgame players (n=10 in each group) watched a series of video images showing simulated sacrifice bunt situations recorded from the catcher`s point of view. The participants wore an eye movement tracker and made a decision about instructing the pitcher where to throw the ball (i.e., toward either the first or second base) by pressing a button at an appropriate time. After each trial, the participants answered a question about the objects to which attention was mainly directed. Results revealed that 1) catchers made better decisions based on higher signal detection sensitivity, compared with fielders and novices; 2) baseball players (catchers and fielders) had a strategy of decision-making to avoid the risk of losing scores due to erroneous decision; and 3) the catchers mainly directed attention to the ball at the time of bat-ball impact, and shifted attention to the pitcher and runner at the time of decision-making, while keeping their gaze on the ball from the time of impact to that of decision-making. These results suggest that catchers demonstrate higher signal detection sensitivity, a more specific judgment bias based on baseball experience, and a more efficient visual search strategy.